The Income Terms of Trade - Dorrance, G. S. (Review of Economic Studies, 1948)
Journal Article The Income Terms of Trade Get access G. S. Dorrance G. S. Dorrance London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 1, 1948, Pages 50–56, https://doi.org/10.2307/2296143 Published: 01 April 1948